Strengthening effective preventive services for refugee populations: toward communities of solution - Griswold, Kim S; Pottie, Kevin; Kim, Isok; Kim, Wooksoo; Lin, Li (Université d'Ottawa | University of Ottawa, 2018)
Abstract Refugee populations have unequal access to primary care and may not receive appropriate health screening or preventive service recommendations. They encounter numerous health care disadvantages as a consequence of low-income status, race and ethnicity, lower educational achievement, varying degrees of health literacy, and limited English proficiency. Refugees may not initially embrace the concept of preventive care, as these services may have been unavailable in their countries of origin, or may not be congruent with their beliefs on health care. Effective interventions in primary care include the appropriate use of culturally and linguistically trained interpreters for health care visits and use of evidence-based guidelines. Effective approaches for the delivery of preventive health and wellness services require community engagement and collaborations between public health and primary care. In order to provide optimal preventive and longitudinal screening services for refugees, policies and practice should be guided by unimpeded access to robust primary care systems. These systems should implement evidence-based guidelines, comprehensive health coverage, and evaluation of process and preventive care outcomes.